2015
DOI: 10.1111/fwb.12610
|View full text |Cite
|
Sign up to set email alerts
|

Turbidity alters pre‐mating social interactions between native and invasive stream fishes

Abstract: 1. Environmental degradation can result in the loss of aquatic biodiversity if impairment promotes hybridisation between non-native and native species. Although aquatic biological invasions involving hybridisation have been attributed to elevated water turbidity, the extent to which impaired clarity influences reproductive isolation among non-native and native species is poorly understood. 2. We examined whether turbidity influences intraspecific and interspecific pre-mating social interactions between invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
(112 reference statements)
0
16
0
Order By: Relevance
“…; Ward and Blum ; Glotzbecker et al. ), little information has been available on the stability and evolution of the swarm over time. Empirical analysis of phenotypic and genetic clines across hybrid swarms over time is arguably a more reliable method for assessing stability, including movement and expansion (Blum , ; Dasmahapatra et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Ward and Blum ; Glotzbecker et al. ), little information has been available on the stability and evolution of the swarm over time. Empirical analysis of phenotypic and genetic clines across hybrid swarms over time is arguably a more reliable method for assessing stability, including movement and expansion (Blum , ; Dasmahapatra et al.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for loss of native biota through biological invasions involving hybridization has risen as human-mediated introduction, and invasions of non-native species have increased over time (Epifanio and Philipp 2000;Allendorf et al 2001;Crispo et al 2011). Although prior studies examining the C. lutrensis x C. venusta hybrid swarm in the Upper Coosa River basin (Walters et al 2008;) have characterized the formation of the swarm, as well as the spatial extent and factors contributing to hybridization Glotzbecker et al 2015), little information has been available on the stability and evolution of the swarm over time. Empirical analysis of phenotypic and genetic clines across hybrid swarms over time is arguably a more reliable method for assessing stability, including movement and expansion (Blum 2002(Blum , 2008Dasmahapatra et al 2002;Buggs 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glotzbecker et al. () showed that elevated turbidity can weaken sexual selection by impairing species recognition between native and invasive stream fishes, thus resulting in formation of hybridization, but they neglected the impact of water turbidity on fish ecology.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of hybrids is thought to have resulted from elevated water turbidity and habitat destruction following the introduction of crayfish Taylor et al 2006). Indeed, experimental studies show that impaired water clarity can alter the premating mechanism of sexual selection to reduce reproductive isolation (Sundin et al 2010;Glotzbecker et al 2015).…”
mentioning
confidence: 99%